2009
DOI: 10.1016/j.virol.2008.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus-2 and its primary cellular receptor—Cryo-EM structure of a heparin complex

Abstract: Adeno-associated virus serotype 2 (AAV-2) is a leading candidate vector for gene therapy. Cell entry starts with attachment to a primary receptor, Heparan Sulfate Proteoglycan (HSPG) before binding to a co-receptor. Here, cryo-electron microscopy provides direct visualization of the virus–HSPG interactions. Single particle analysis was performed on AAV-2 complexed with a 17kDa heparin fragment at 8.3Å resolution. Heparin density covers the shoulder of spikes surrounding viral 3-fold symmetry axes. Previously i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
153
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(157 citation statements)
references
References 68 publications
(84 reference statements)
2
153
0
Order By: Relevance
“…7C; also, see Movie S1 in the supplemental material). Residues 585 and 588 in AAV2 are located on the side of the protrusion and are critical for heparan sulfate recognition (15)(16)(17)97), transduction efficiency, and tissue tropism, suggesting a connection between protein dynamics and receptor binding. Distance measurements from the sites of cleavage to the icosahedral 2-, 3-, and 5-fold axes confirmed that the residues clustered near the 3-fold axes at an average distance of ϳ25 Å (Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…7C; also, see Movie S1 in the supplemental material). Residues 585 and 588 in AAV2 are located on the side of the protrusion and are critical for heparan sulfate recognition (15)(16)(17)97), transduction efficiency, and tissue tropism, suggesting a connection between protein dynamics and receptor binding. Distance measurements from the sites of cleavage to the icosahedral 2-, 3-, and 5-fold axes confirmed that the residues clustered near the 3-fold axes at an average distance of ϳ25 Å (Fig.…”
Section: Figmentioning
confidence: 99%
“…AAV2 has also received the most attention with respect to dissecting the mechanisms of cellular entry and trafficking. For this serotype, attachment to the host cell surface is mediated by heparan sulfate proteoglycans (HSPG) (15)(16)(17)(18)97), and several secondary receptors or coreceptors have been reported to mediate entry via dynamin-dependent clathrin-mediated endocytosis (19)(20)(21)(22)25). AAV2 may also enter cells via a dynamin-and clathrin-independent route (26).…”
mentioning
confidence: 99%
“…The AAV capsid surface features that are unique to AAV5-shorter 3-fold protrusions, extended VR-VII, and smaller HI loop-contain amino acid residues or are proximate to capsid regions reported to play essential roles in the AAV life cycle. For example, residues within VR-IV, VR-V, and VR-VIII which make up the 3-fold protrusions have been reported to control glycan receptor attachment (VR-V and VR-VIII for AAV2 and VR-V for AAV9) (90)(91)(92)(93)122), transduction (VR-IV, VR-V, and VR-VIII in AAV2, VR-VIII in AAV8, and VR-IV, VR-V, and VR-VIII in AAV9) (94)(95)(96)(97)(98)(99) and antigenic phenotypes (VR-IV, VR-V, and VR-VIII in AAV2 and VR-VIII in AAV8 (97,100,101). These regions have similar roles in AAV5.…”
Section: Fig 2 Aav Capsid Surfaces (A Cmentioning
confidence: 99%
“…A novel primate AAV variant, AAV(VR-942), which also uses HS as a primary receptor, contains a K528 residue that is predicted to be structurally equivalent to the AAV6 K531 residue (57) ( Table 4). AAV2 also binds HS (60) but lacks this basic residue and, instead, utilizes two critical residues, R585 and R588, along with R484, R487, K527, and K532 (minor contributors) (AAV2 VP1 numbering) (Table 4) for this interaction (32,38,49,50,60). Except for R487, these residues form a basic footprint on the surface (Fig.…”
Section: Vol 84 2010 Structure Of Aav6 12949mentioning
confidence: 99%